ANALISIS KUALITAS AIR KONSUMSI PENDERITA PENYAKIT KULIT DI PONDOK PESANTREN AL HIKMAH BENDA KECAMATAN SIRAMPOG KABUPATEN BREBES - Yeni Purwiyantini; Ian Yulianti; Masturi Masturi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Water is major requirement for living process in the earth, there is not human existence if there is not water in the earth. But, water can be a disaster if it is not in the right condition, both the quality and the quantity. The aim of this research is to describe the water consumption quality of sufferers with skin diseases in pondok pesantren Al Hikmah Benda Sirampog Brebes. The kind of this research is descriptive survey research. The population of this research is all the water in the baths that are used by people with skin diseases in pondok pesantren Al Hikmah, and the samples are 10 baths itself, or using total sampling. And the data analysis of this research uses univariat analysis. The result of this research shows that water quality based on physic parameters such as color,and turbidity 40% eligible, while bacteriologist parameter for total coliform 100% ineligible. For that case, it is important for the comunity and goverment to make qualified clean water facilities, especially for the baths so both of quality and quantity of the water are qualified/eligible for the health of all the students in Al Hikmah Boarding School. Keywords: Water Consumption , Skin Diseases.